Activated Carbon and Phosphorus Application Influences the Growth of Continuously Replanted Asparagus (Asparagus Officinalis L.) (Global Journal of Science Frontier Research, 2013)
The influences of activated carbon (AC) and phosphorus (P) to asparagus growth were assessed under laboratory conditions. The asparagus cultivar; Gijnlim (G) of the European origin, were cultivated in different continuous replanting system. AC was incorporated into sandy soil, was amended with 15 years old root residue (RR) before the sowing of asparagus for the first, second (first replanting), third (second replanting) and fourth (third replanting) time of continuous planting. In all the planting, P was applied weekly basis at P0 (0), P1 (7.5), P2 (15.5) and P3 (22.5) mg•l -1 . After third replanting, in without AC, P0 and with RR treatment, root biomass inhibited (P
Keywords: asparagus; activated carbon; growth; nutrient uptake; phosphorus; root residue